Mechanical properties and energy evolution of outburst coal seams under different load regimes - Zhang Tianjun; Wu Jiaokun; Wang Gang; Chen Yong; Ding Hong; Ma Hongyu; Yang Jie (Energy Science & Engineering)
Abstract Coal elasticity and gas expansion are important factors for coal and gas outburst. During the outburst process, the elastic strain energy of coal is mainly released from the stress region, and the gas expansion energy near the working face is larger, and it is not a continuous release process. To reveal the mechanical characteristics and energy evolution of outburst coal seam, uniaxial and triaxial compression tests were carried out on outburst coal seam samples under different loading methods. The experimental results show that the elastic characteristics become more obvious with the increase of loading rate, the peak strain increases, the elastic modulus is linearly related with the loading rate，and the overall degree of fragmentation increases with the increase of loading rate, which is consistent with the severity of macroscopic coal failure. The failure mode of coal under uniaxial compression conditions is often manifest as brittle failure. The strength characteristics of coal under different loading rates comply with the Mohr‐Coulomb criterion, and the peak strength is linearly related to the failure time and loading rate. With the increasing confining pressure causes the failure of coal samples to transition from ductile to brittle, and the failure mode develops from local shear to overall splitting. The elastic energy evolution curve is consistent with its stress‐strain curve. With the increase of confining pressure, the limiting elastic energy and peak total energy increase in a quasi‐linear manner. The accumulated limit elastic energy plays an important role in the failure of coal samples, and the macroscopic manifestation thereof is that the coal samples fail more severely under high confining pressure conditions than under low confining pressure conditions. The research results are of great significance for the comprehensive prevention and control of coal and gas outburst.